The Development of a Live Air Cleaner as Indoor Garden for an Unventilated Air Conditioned Room - Prasasto Satwiko; YP Suhodo; Israni Silvia S; A Djoko Istiadji; Nimas Sekarlangit; Dewi Retnaningati (Departement of Architecture, Universitas Islam Indonesia, 2020)
Urban temperatures continue to increase due to urban heat island and global warming. Air temperatures in warm, humid tropical cities have exceeded 32oC. To achieve thermal comfort in buildings, people adopted air conditioners (ACs) that can consume more than 40% of the building's electrical energy. Air conditioning is often not accompanied by a supply of fresh outdoor air to minimize heat gain from the warm outdoor air. In that unventilated room, the CO2 concentration easily exceeds 1,000 ppm and causes discomfort. Plants such as Dracaena sanderiana require CO2 for photosynthesis. At the same time, they produce O2. Dracaena sanderiana has the potential to keep CO2 concentrations in the room for not exceeding the comfort limit. That plant can be integrated into architectural elements, both interior and exterior (combined with windows or facades), in the form of a